(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study investigates and compares consumer preferences for perishable products between urban and rural markets in Maharashtra, India, focusing on three key dimensions: quality and freshness, health and nutrition awareness, and packaging and presentation. The objectives of the study are to identify any ‘significant difference’ in preferences between urban and rural consumers and to provide recommendations for businesses and policymakers based on the findings. A sample of urban and rural customers from various localities in Maharashtra was surveyed using a structured questionnaire, with responses quantified on a ten-point ordinal scale. Statistical analysis, including t-tests and descriptive statistics, was employed to analyse the data and determine any significant disparities in preferences between the two consumer groups. The results of the study reveal notable differences in consumer preferences between urban and rural markets across all three dimensions examined. Urban consumers tend to prioritize factors such as freshness, brand reputation, and attractive packaging, reflecting their convenience-oriented and health-conscious lifestyles. In contrast, rural consumers exhibit preferences for traditional methods, locally sourced products, and functional packaging, reflecting their cultural values and community-oriented approach to consumption. Several recommendations are proposed to better cater to the diverse needs of consumers in both urban and rural settings. Businesses operating in the perishable products sector are advised to customize their product offerings and marketing strategies to align with the preferences and values of each consumer segment. Additionally, attention should be given to packaging and presentation, ensuring that designs appeal to the aesthetic sensibilities of urban consumers while also reflecting the authenticity and heritage valued by rural consumers. Collaborative efforts between urban and rural producers, suppliers, and retailers are recommended to leverage the strengths of both supply chains and foster greater inclusivity in the market